Dominant currencies: How firms choose currency invoicing and why it matters - Mary Amiti; Oleg Itskhoki; Jozef Konings (National Bank of Belgium, 2018)
Large movements in exchange rates have small effects on the prices of internationally traded goods. Using a new dataset on currency invoicing of Belgian firms, we study how the currency of invoicing interacts with firm characteristics in shaping the extent of exchange rate pass-through at different time horizons. The US dollar and the Euro are the dominant currencies in both Belgium's exports and imports, with substantial variation in currency choice across firms and products even within narrowly defined manufacturing industries. We find that smaller, nonimport-intensive firms tend to denominate their exports in euros (producer currency pricing) and exhibit nearly complete exchange-rate pass-through into destination currency prices at all horizons. In contrast, the largest most import-intensive firms, and in particular with imports denominated in US dollars, tend to also denominate their exports in US dollars (dominant currency pricing) and exhibit very low pass-through in the short run, which gradually increases to 40-50% pass-through at the annual horizon. We show that these empirical patterns are in line with the predictions of a theoretical framework featuring heterogeneous firms with variable markups, endogenous international input sourcing and staggered price setting with endogenous currency choice. We plan to use a variant of a such model, disciplined with the Belgian firm-level data, for counterfactual analysis of the gradual increase in the use of the euro in international trade flows.
Keywords: 330